Gestational and Non-gestational Trophoblastic Disease. Guideline of the DGGG, OEGGG and SGGG (S2k Level, AWMF Registry No. 032/049, December 2015) - Tempfer, C. (Geburtshilfe Frauenheilkd, 2016)
Purpose: The aim was to establish an official interdisciplinary guideline, published and coordinated by the German Society of Gynecology and Obstetrics (DGGG). The guideline was developed for use in German-speaking countries. In addition to the Germany Society of Gynecology and Obstetrics, the guideline has also been approved by the Swiss Society of Gynecology and Obstetrics (SGGG) and the Austrian Society of Gynecology and Obstetrics (OEGGG). The aim was to standardize diagnostic procedures and the management of gestational and non-gestational trophoblastic disease in accordance with the principles of evidence-based medicine, drawing on the current literature and the experience of the colleagues involved in compiling the guideline. Methods: This s2k guideline represents the consensus of a representative panel of experts with a range of different professional backgrounds commissioned by the DGGG. Following a review of the international literature and international guidelines on trophoblastic tumors, a structural consensus was achieved in a formalized, multi-step procedure. This was done using uniform definitions, objective assessments, and standardized management protocols. Recommendations: The recommendations of the guideline cover the epidemiology, classification and staging of trophoblastic tumors; the measurement of human chorionic gonadotropin (hCG) levels in serum, and the diagnosis, management, and follow-up of villous trophoblastic tumors (e.g., partial mole, hydatidiform mole, invasive mole) and non-villous trophoblastic tumors (placental site nodule, exaggerated placental site, placental site tumor, epitheloid trophoblastic tumor, and choriocarcinoma).